2016
DOI: 10.4103/0974-2700.185274
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in trauma patients with active arterial bleeding managed by embolization or surgical packing: An observational cohort study of 66 patients

Abstract: Objective:Exsanguination due to coagulopathy and vascular injury is a common cause of death among trauma patients. Arterial injury can be treated either by angiography and embolization or by explorative laparotomy and surgical packing. The purpose of this study was to compare 30-day mortality and blood product consumption in trauma patients with active arterial haemorrhage in the abdominal and/or pelvic region treated with either angiography and embolization or explorative laparotomy and surgical packing.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Marzi et al [16] conducted a literature review on pelvic fracture management in 2009 and concluded that pelvic packing should be used for hemodynamically unstable patients who do not respond to resuscitative fluids and those requiring continuous fluids to maintain hemodynamic stability. Many studies [9, 11, 1618] have compared PP to angioembolization as a treatment modality, leading to some [4, 15, 1921] concluding that that the two approaches should not be compared and should instead be viewed as complementary. In 2018, Muntasar et al [9] found insufficient evidence to support superiority of one treatment modality over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Marzi et al [16] conducted a literature review on pelvic fracture management in 2009 and concluded that pelvic packing should be used for hemodynamically unstable patients who do not respond to resuscitative fluids and those requiring continuous fluids to maintain hemodynamic stability. Many studies [9, 11, 1618] have compared PP to angioembolization as a treatment modality, leading to some [4, 15, 1921] concluding that that the two approaches should not be compared and should instead be viewed as complementary. In 2018, Muntasar et al [9] found insufficient evidence to support superiority of one treatment modality over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion is an imperative method to resuscitate patients and is an indispensable step within peri-operation. There were 10 studies comparing preoperative transfusion between PP and AE [3,21,22,[24][25][26][27][28][29][30] and two studies on PP and REBOA [31,32] , which showed much more transfusion in PP group than in EI group (MD=2.53, 95% CI [0.01, 5.06], Fig. 3).…”
Section: Basic Characteristics Of Included Patientsmentioning
confidence: 99%
“…After reviewing the full text, 15 studies met the inclusion criteria in the meta-analysis [3,5,[21][22][23][24][25][26][27][28][29][30][31][32][33]. All studies had a low risk of bias for selective blinding.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…All the above considerations must take into account the possible disadvantages in the transportation of a severely injured patient to the angiographic room [ 57 ]. However, the increasingly widespread use of hybrid OR, where trauma surgeons, orthopedic surgeons, and interventional radiologists can work together, is progressively enabling the simultaneous or alternate performance of the initial assessment, resuscitation, damage control surgery, and endovascular procedures, without the need to transfer the patient to the radiological room or the OR [ 9 ].…”
Section: Treatment For Hemorrhage In Pelvic Fracture: State Of the Artmentioning
confidence: 99%